Co-creating changes to achieve decent work conditions in the New Zealand fishing industry. (August 2022) - Kartikasari, Ani; Stringer, Christina; Henderson, Guye
In 2014, New Zealand enacted the Fisheries (Foreign Charter Vessels and Other Matters) Amendment Act in response to ongoing labour abuses on board South Korean vessels in New Zealand's foreign charter vessel sector. Importantly, the legislation expresses the universality of the International Labour Organization's Decent Work Agenda: all member countries must pursue policies based on the strategic objectives of equality, dignity, safe working conditions and that workers are protected from exploitation. The Act was in response to the identification of widespread labour abuses in this sector. In June 2011, the extent of the abuses came to light when 32 Indonesian crewmen of the Oyang 75 walked off their vessel. In this paper, we explore how a range of stakeholders worked organically to bring about change. We do this qualitatively by combining semi-structured interview (with over 160 Indonesian migrant crewmen between 2011 and 2017), observation and document analysis. We analyse our data through the lens of participatory action research which provides a framework to document the processes of who was involved, the cycles of change, what was achieved in each cycle, and importantly the platform for change. Specifically, we look at how stakeholders – the crew themselves, their advocates, academics, non-governmental organisations, journalists, activists, among others – all played a part in achieving legislated protections.